Ontogeny of NHE8 in the rat proximal tubule - Becker, Amy M. (2007)
Proximal tubule bicarbonate reabsorption is primarily mediated via the Na(+)/H(+) exchanger, identified as NHE3 in adults. Previous studies have demonstrated a maturational increase in rat proximal tubule NHE3 expression, with a paucity of NHE3 expression in neonates, despite significant Na(+)-dependent proton secretion. Recently, a novel Na(+)/H(+) antiporter (NHE8) was identified and found to be expressed on the apical membrane of the proximal tubule. To determine whether NHE8 may be the antiporter responsible for proton secretion in neonates, the present study characterized the developmental expression of NHE8 in rat proximal tubules. RNA blots and real-time RT-PCR demonstrated no developmental difference in the mRNA of renal NHE8. Immunoblots, however, demonstrated peak protein abundance of NHE8 in brush border membrane vesicles of 7- and 14-day-old compared with adult rats. In contrast, the level of NHE8 expression in total cortical membrane protein was higher in adults than in neonates. Immunohistochemistry confirmed the presence of NHE8 on the apical membrane of the proximal tubules of neonatal and adult rats. These data demonstrate that NHE8 does undergo maturational changes on the apical membrane of the rat proximal tubule and may account for the Na(+)-dependent proton flux in neonatal proximal tubules.